Anti-VEGF therapy for diabetic macular edema: up-to-date approaches to the management of patients with high and low baseline functional parameters - E.V. Bobykin (РМЖ "Клиническая офтальмология")
E.V. Bobykin Ural State Medical University, Yekaterinburg, Russian Federation Diabetic macular edema (DME) is a serious complication of diabetes mellitus (DM) and a vision-threatening condition which can lead to irreversible blindness. Its prevalence correlates with the number of cases of DM and diabetic retinopathy and demonstrates a stable upward trend. Though modern medicine has made tremendous strides and developed several options for DME treatment which comply with the efficacy and safety criteria fr om a perspective of evidence-based medicine, DME remains a challenge in the clinical practice. There is no doubt that the key role is played by anti-angiogenic (anti-VEGF) therapy which has become the gold standard treatment for DME and is supported by a strong evidence base. However, some aspects of this method application are understudied. Thus, most of the randomized clinical studies (RCSs) of anti-VEGF therapy included patients with the "averaged" baseline values of visual acuity (within the range of 23–79 letters using ETDRS chart / 0.0 6–0.7 in decimal system). But in real clinical practice ophthalmologists often observe atypical DME cases wh ere the baseline visual acuity values fall outside the range described in RCSs. The present literature review is aimed at considering tactics of the rational management of patients with atypically low and high baseline visual functions and provides analysis of the recent publications in which the outcomes of anti-VEGF therapy are discussed in the context of this problem. Keywords: macular edema, anti-VEGF therapy, diabetic retinopathy, diabetes, diabetic macular edema, high visual acuity, low visual acuity. For citation: Bobykin E.V. Anti-VEGF therapy for diabetic macular edema: up-to-date approaches to the management of patients with high and low baseline functional parameters. Russian Journal of Clinical Ophthalmology. 2022;22(3):181–186 (in Russ.). DOI: 10.32364/2311-7729-2022-22-3-181-186.